2023
DOI: 10.1101/2023.02.07.527440
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Dual Action of Human Antibodies Specific toPlasmodium falciparumPfRH5 and PfCyRPA: Blocking Invasion and Inactivating Extracellular Merozoites

Abstract: The Plasmodium falciparum reticulocyte-binding protein homolog 5 (PfRH5) is the current leading blood-stage malaria vaccine candidate. PfRH5 functions as part of the pentameric PCRCR complex containing PTRAMP, CSS, PfCyRPA and PfRIPR, all of which are essential for infection of human red blood cells (RBCs). To trigger RBC invasion, PfRH5 engages with RBC protein basigin in a step termed the RH5-basigin binding stage. Although we know increasingly more about how antibodies specific for PfRH5 can block invasion,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The second clone, R5.008, is itself GIA-positive, with an epitope that overlaps the basigin binding site 36,50,51 . Interestingly, recent live cell imaging has confirmed the synergy of the R5.008+Cy.009 mAb combination and suggested that inactivation of uninvaded parasites by these antibody combinations may function as a second inhibitory mechanism alongside blockade of basigin receptor binding 52 . We did not observe inter-antigen synergy with R5.016 unlike previous reports 38 , highlighting the complexity of synergy between antibodies against specific epitope regions of RH5 with anti-CyRPA and -RIPR clones.…”
Section: Discussionmentioning
confidence: 99%
“…The second clone, R5.008, is itself GIA-positive, with an epitope that overlaps the basigin binding site 36,50,51 . Interestingly, recent live cell imaging has confirmed the synergy of the R5.008+Cy.009 mAb combination and suggested that inactivation of uninvaded parasites by these antibody combinations may function as a second inhibitory mechanism alongside blockade of basigin receptor binding 52 . We did not observe inter-antigen synergy with R5.016 unlike previous reports 38 , highlighting the complexity of synergy between antibodies against specific epitope regions of RH5 with anti-CyRPA and -RIPR clones.…”
Section: Discussionmentioning
confidence: 99%